PENYAKIT JAMUR AKAR PUTIH DAN COKELAT PADA JAMBU METE DAN STRATEGI PENGENDALIANNYA - Rita Harni; Widi Amaria (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The development of cashew (Anacardium occidentale) has a great opportunity, because the national contribution of cashew is still relatively small in world markets. Center prodcuction of the crop in of cashew in eastern Indonesia such as Southeast Sulawesi, South Sulawesi, NTB and NTT. In increasing productivity of cashew crop in Indonesia, there are symptoms of white and brown roots diseases which can cause the death of cashew plant. White Root Rot Fungus (WRF) is caused by Rigidophorus lignosus and Rigidophorus microporus, whereas Brown Root Rot Fungus (BRF) is caused by Phellinus noxius. The symptoms of both diseases are rizomorf in roots and base of the stem, when they attack on the advanced stage, leaves become yellow, fall, dried, canopy only branches and subsequent plant death. WRF and BRF can survive in soil for many years and is a source of infection for healthy cashew. Transmission of the disease through contact with the roots of diseased plants and healthy plants. Control WRF and BRF recommended in an integrated manner, i.e. resistant varieties, technical culture, biological agents, mechanical and chemical.